Studi Literatur : Pengaruh Suhu terhadap Ikan Nila (Oreochromis niloticus) - Cahyanti, Yumna; Awalina, Irsha (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2022)
Tilapia is one example of fish that is successfully cultivated in the world. Tilapia can live in deep and wide waters as well as in narrow and shallow ponds, and can live in rivers. The main environmental and management factors that affect the survival and growth of fish are dissolved oxygen levels, temperature, pH, feeding rate, and others. This study aims to determine the effect of temperature on tilapia (Orechromis niloticus). The method used in this research is a literature study (systematic review) by analyzing several scientific articles that are relevant to the study being discussed. The results of this study are known that temperature is very influential on several aspects of life, namely the level of survival, appetite, level of stability of the body for disease, growth rate, fish movement, viscosity and blood flow, oxygen consumption, leukocyte count, glucose level. in the blood, the number of erythrocytes, the number of platelets, the reaction of changing ammonium to ammonia, seed maintenance, tilapia weight, spermatogenesis stage in male individuals, hemoglobin concentration, feminization and masculinization of gonads, gastric evacuation rate, number of egg production, swimming speed, metabolic rate, response to feeding, the level of infertility in female fish, tilapia seed weight, fish stress level, the mechanism for determining the number of sex ratios, ovarian structure, and testicular structure. The conclusion of this study is that temperature greatly influences the life of tilapia (Oreochromis niloticus).